The Pharmacologic Treatment of Stuttering and Its Neuropharmacologic Basis - Maguire, Gerald A.; Nguyen, Diem L.; Simonson, Kevin C.; Kurz, Troy L. (Frontiers in Neuroscience, 2020)
Stuttering is a DSM 5 psychiatric condition for which no medications are FDA-approved to treat. A growing body of evidence suggests that dopamine antagonist medications are effective in reducing the severity of stuttering symptoms. Stuttering shares many similarities to Tourette's Syndrome in that both begin in childhood, follow a similar male to female ratio of 4:1, respond to dopamine antagonists, and symptomatically worsen with dopamine agonists. In recent years, advances in the neurophysiology of stuttering have helped further guide pharmacological treatment. A newer medication with a novel mechanism of action, selective D1 antagonism, is currently being investigated in FDA trials for the treatment of stuttering. D1 antagonists possess different side-effect profiles than D2 antagonist medications, and may provide a unique option for those who stutter. In addition, VMAT-2 inhibitors alter dopamine transmission in a unique mechanism of action that offers a promising treatment avenue in stuttering. This review seeks to highlight the different treatment options to help guide the practicing clinician in the treatment of stuttering.